2011
DOI: 10.1103/physreva.83.053422
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the electron initial longitudinal velocity on the nonsequential double-ionization process

Abstract: The effect of initial longitudinal velocity of the first tunneling electron on the nonsequential double-ionization (NSDI) process is studied using a semiclassical model. Our analysis shows that nonzero initial longitudinal velocity affects two distinct typical trajectories [single-return collision (SRC) and multiple-return collision (MRC)] in the NSDI process in different ways: for SRC, the yield in the center part of the correlation momentum distribution is reduced; for MRC, the tunneling time of the first el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…Very recently, this effect of the initial longitudinal momentum of the tunneling electron on its final momentum distribution was also observed in the single ionization of the molecular ion H 2 þ by using a circularly polarized ultrashort laser pulse [28]. Interestingly, the initial longitudinal momentum of the first tunneling electron was found to be important for (e) (f) understanding the entire nonsequential double-ionization process [29].…”
mentioning
confidence: 74%
“…Very recently, this effect of the initial longitudinal momentum of the tunneling electron on its final momentum distribution was also observed in the single ionization of the molecular ion H 2 þ by using a circularly polarized ultrashort laser pulse [28]. Interestingly, the initial longitudinal momentum of the first tunneling electron was found to be important for (e) (f) understanding the entire nonsequential double-ionization process [29].…”
mentioning
confidence: 74%
“…It is clear that the electron emission is anticorrelated at lower laser intensities, but becomes correlated as the laser intensity increases. Such a transition is observed in [13,15] and is attributed to quantum tunnelling effect [16,17] or multiple recollision during the ionization process of the second electron [18][19][20]. However, recently we showed that the quantum tunnelling effect is not always important in NSDI [33].…”
Section: Resultsmentioning
confidence: 96%
“…It has been shown that the longitudinal momentum distribution exhibits an anticorrelation feature at lower laser intensities [13,14], but a correlation feature when the laser intensity is higher than the recollision threshold [15]. Such a transition is attributed to the quantum tunnelling effect [16,17] or the multiple recollision during the ionization process of the second electron [18][19][20]. Here the anticorrelation feature denotes the two electrons emitted back-to-back so that the second and the fourth quadrants of the momentum diagram are highlighted, while the correlation feature means the side-byside emission being dominant.…”
Section: Introductionmentioning
confidence: 99%
“…The calculation procedure is based on a wellverified numerical method, which has been employed successfully to understand many aspects of the NSDI process, e.g., the knee structure in the distribution of the yield of double-charged ions versus intensity; the maxima in the 1st and 3rd quadrants of the EMCD etc. [52][53][54][55].…”
Section: Discussionmentioning
confidence: 99%
“…In this model [52][53][54][55][56], one electron is released at the outer edge of the field-suppressed Coulomb potential through tunneling with a rate given by the ADK formula [57]. The subsequent evolution of the tunneled and the bound electron is determined by Newton's equation of motion (in atomic units, e = m = = 1)…”
Section: Discussionmentioning
confidence: 99%